In the expansion of


In the expansion of $(x+a)^{n}$ if the sum of odd terms is denoted by 0 and the sum of even term by E. Then prove that

(i) $\mathrm{O}^{2}-\mathrm{E}^{2}=\left(\mathrm{x}^{2}-\mathrm{a}^{2}\right)^{n}$

(ii) $40 E=(x+a)^{2 n}-(x-a)^{2 n}$


(i) We know that

$(x+a)^{n}={ }^{n} C_{0} x^{n}+{ }^{n} C_{1} x^{n-1} a^{1}+{ }^{n} C_{2} x^{n-2} a^{2}+{ }^{n} C_{3} x^{n-3} a^{3}+\ldots$

Sum of odd terms,

$O={ }^{n} C_{0} x^{n}+{ }^{n} C_{2} x^{n-2} a^{2}+\ldots$

And also sum of even terms

$E={ }^{n} C_{1} x^{n-1} a+{ }^{n} C_{3} x^{n-3} a^{3}+\ldots$

Since $(x+a)^{n}=0+E$




(ii) $40 E=(O+E)^{2}-(O-E)^{2}$

$=(x-a)^{2 n}-(x-a)^{2 n}$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now